Kajian Status Unsur Hara Makro Tanah (N, P, Dan K) di Profil Tanah Lahan Hutan, Wanatani, dan Tegalan - Parjono Parjono (Musamus AE Featuring Journal, 2019)
This study aims to determine the macronutrients status of Nitrogen (N), Phosphorus (P), and Potassium (K), and soil acidity (pH) in the use of forest land, agroforestry, and dryland agriculture. The study was conducted by taking soil samples at four soil horizons (Ao or Ap, A1 or A2, B1, and B2) in each land use. Soil analysis in the laboratory to determine the concentration of N, P, K, organic C, and soil pH. Data analysis was carried out descriptively. The results showed that the distribution of N, P, and K on forest land and agroforestry decreased based on the depth of the land horizon, while the dryland agriculture has fluctuated. On forest land the concentration of N = 0.20-1.11%, P = 5.81-6.62 ppm, and K = 0.19-1.52%. Agroforestry N = 0.06-0.22%, P = 3.66-4.70 ppm, and K = 0.11-0.78 ppm. Whereas in the dryland agriculture concentration, N = 0.18-0.51%, P = 5.61-6.68 ppm, and K = 0.11-0.37 ppm. Organic matter, the intensity of tillage plays an important role in the distribution pattern and concentration of N, P, and K in the soil. Agroforestry systems can be a solution to the stability of soil fertility.